(untitled) (Archive of Conferences, 2020)
The article discusses the issue of humanization of the education system in the Republic of Uzbekistan, reveals the essence of the concept of "humanization" in the historical aspect and in relation to modern conditions, outlines the directions of reforming the education system based on its humanization and democratization.